1996
DOI: 10.1073/pnas.93.23.13194
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of measles virus glycoproteins with the surface of uninfected peripheral blood lymphocytes induces immunosuppressionin vitro

Abstract: A marked suppression of immune function has long been recognized as a major cause of the high morbidity and mortality rate associated with acute measles. As a hallmark of measles virus (MV)-induced immunosuppression, peripheral blood lymphocytes (PBLs) isolated from patients exhibit a significantly reduced capacity to proliferate in response to mitogens, allogens, or recall antigens. In an in vitro system we show that proliferation of naive PBLs [responder cells (RCs)] in response to a variety of stimuli was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
164
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(174 citation statements)
references
References 32 publications
9
164
1
Order By: Relevance
“…MV infection has been shown to affect DC function; MVinfected DCs are unable to stimulate a mixed lymphocyte reaction and can induce lymphocyte unresponsiveness through expression of MV glycoproteins [40,41]. Therefore, it is possible that MV interferes with the cross-presentation antigen-processing pathway of primary LCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MV infection has been shown to affect DC function; MVinfected DCs are unable to stimulate a mixed lymphocyte reaction and can induce lymphocyte unresponsiveness through expression of MV glycoproteins [40,41]. Therefore, it is possible that MV interferes with the cross-presentation antigen-processing pathway of primary LCs.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, immature LCs were found susceptible for MV [26], but they might have been more activated as others showed that mechanical stress facilitates LC activation and MV infection [25]. Therefore, differences in activation status of LCs determine susceptibility to MV.MV infection has been shown to affect DC function; MVinfected DCs are unable to stimulate a mixed lymphocyte reaction and can induce lymphocyte unresponsiveness through expression of MV glycoproteins [40,41]. Therefore, it is possible that MV interferes with the cross-presentation antigen-processing pathway of primary LCs.…”
mentioning
confidence: 99%
“…Thus, accumulating evidence strongly links immunosuppression and lymphopenia not only to direct effects following infection and subsequent destruction of signalling lymphocytic activating molecule (SLAM)-positive immune cells and precursor cells in the acute phase of the infections, but also to indirect effects modulating the host innate and adaptive immune systems (Cruz et al, 2006;Devaux et al, 2008;Heaney et al, 2005;Karp et al, 1996;Schlender et al, 1996;Tatsuo et al, 2001;von Messling et al, 2006). The relative impact on virulence of the different mechanisms modulating the immune system in vivo is, however, not yet clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral blood lymphocytes (PBLs) isolated from measles patients show a reduced proliferation capacity in response to polyclonal stimulation (Hirsch et al, 1984 ;Whittle et al, 1978) possibly due to a cell cycle arrest in the end of the G1 phase (McChesney et al, 1987(McChesney et al, , 1988. Even uninfected PBLs were shown to exhibit decreased proliferation in presence of cells that express measles glycoproteins (Niewiesk et al, 1997 ;Schlender et al, 1996). In addition, MV infection also influences the maturation, survival and functioning of dendritic cells (DCs) (Fugier-Vivier et al, 1997 ;Grosjean et al, 1997 ;Schnorr et al, 1997).…”
mentioning
confidence: 99%